1988
DOI: 10.2307/3344877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Practice Conditions on Advanced Instrumentalists' Performance Accuracy

Abstract: The purpose of this study was to examine the relative effects of five practice conditions on instrumentalists' performance of a musical composition. The authors assigned 60 college music students to one of five practice conditions and asked them to perform the composition after a brief practice session. Practice conditions were modeling, singing, silent analysis, free practice, and control. The authors evaluated each subject's performance in terms of correct notes, rhythms, phrasing or dynamics, articulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 5 publications
7
66
1
3
Order By: Relevance
“…This suggests that direct teacher modelling, without verbal comments, may be the most effective teaching strategy to improve the accuracy of student playing. Rosenthal, Wilson, Evans, and Greenwalt (1988) reached similar conclusions, when they examined the relationship of five practice conditions (modelling, singing, silent analysis, free practice and control-practice) to the performance accuracy of advanced wind players. In more recent studies Linklater (1997) found that students improved more in home practice after watching the model videotape than after listening to the audio model or the accompaniment part only, and Hewitt (2001) showed that listening to a model improved student playing in the areas of tone, rhythm and interpretation, but not intonation or accuracy.…”
Section: Teacher Modellingmentioning
confidence: 89%
See 1 more Smart Citation
“…This suggests that direct teacher modelling, without verbal comments, may be the most effective teaching strategy to improve the accuracy of student playing. Rosenthal, Wilson, Evans, and Greenwalt (1988) reached similar conclusions, when they examined the relationship of five practice conditions (modelling, singing, silent analysis, free practice and control-practice) to the performance accuracy of advanced wind players. In more recent studies Linklater (1997) found that students improved more in home practice after watching the model videotape than after listening to the audio model or the accompaniment part only, and Hewitt (2001) showed that listening to a model improved student playing in the areas of tone, rhythm and interpretation, but not intonation or accuracy.…”
Section: Teacher Modellingmentioning
confidence: 89%
“…Another practice strategy is practising away from the instrument without moving a muscle. Research has shown that mental rehearsal is effective (Rosenthal et al, 1988;Pace, 1992) and can improve memory and heighten sensory awareness (Connoly & Williamon, 2004;Tannhauser, 1999).…”
Section: Practisingmentioning
confidence: 99%
“…Modeling was credited with improving pitch accuracy, although not significantly, and participants who engaged in silent practice scored higher than the model group for rhythmic accuracy (Rosenthal et al, 1988). In another study that involved the use of practice tapes with high school instrumentalists, Henley (2001) determined that the students who used modeling tapes were better at learning rhythms and mastering tempo, but results about pitch discrimination were inconclusive.…”
Section: Categories Of Practicementioning
confidence: 99%
“…Mental practice has been considered as an effective practice strategy by a few authors (Barry & Hallam, 2002;Barry & McArthur, 1994;Connolly & Williamon, 2004;Rosenthal et al, 1988). Several researchers have discovered that mental practice may be the most effective when combined with physical practice (Brooks, 1995;Coffman, 1990;Ross, 1985).…”
Section: Types Of Practice Strategiesmentioning
confidence: 99%
See 1 more Smart Citation